Britain and Africa - Kirkwood, Kenneth (Johns Hopkins University Press, 2022)
Originally published in 1965. This book is about the association between Britain and Africa. The book begins with the British entry into Africa and the Indian Ocean and the establishment of the principal foci of power before 1914. The book next treats the quarter century from the First World War until the outbreak of the Second. The book then discusses the period of the Second World War, its aftermath, and the time period contemporaneous with the book's publication. The author's personal experiences and observations shortly before and during the Second World War in different parts of Africa convinced him at the time that the years 1939–1945 marked a decisive watershed. After the historical chapters, the author examines the three major zones of contemporary sub-Saharan Africa. The final chapter considers the major international associations of which Britain is a member and with which it operates in African affairs in the aftermath of colonialism.